Probing Bonding and Dynamics at Heterogeneous Adsorbate/Graphene Interfaces - (:unkn) unknown (My University, 2013)
Graphene-based materials are becoming an astoundingly promising choice for many relevant technological and environmental applications. Deriving graphene from the reduction of graphene oxide (GO) is becoming a popular and inexpensive route toward the synthesis of these materials. While the desired product from GO reduction is pristine graphene, defects and residual oxygen functional groups inherited from the parent GO render reduced graphene oxide (RGO) distinct from graphene. In this work, the structure and bonding for GO and RGO is investigated to the end of a working understanding of the composition and properties of these materials. In situ selected area electron diffraction and ex situ IR microspectroscopy are used to study, respectively, thermal and chemical reduction of GO. The residual oxygen functional groups are found to be predominantly epoxide, C-O-C, bonded oxygen. The role of these oxygen functional groups and the collective RGO in gas sensing applications is investigated by performing in situ IR spectromicroscopy studies of molecular adsorption onto RGO. NO2 and NH3 are the target molecules of interest; NH3 due to its widespread use in industry and NO2 is a a common byproducts in combustion reactions. Following adsorption of both molecules, numerous species are identified on the surface due to the heterogeneity of the substrate. Residual epoxide groups participate in reactions with the target molecules to produce additional surface species that have varying impacts on the conductivity of the substrate.
Keywords: Adsorption; Graphene; Infrared; Micrsocopy